Therapeutic education for empowerment and engagement in patients with Parkinson’s disease: A non-pharmacological, interventional, multicentric, randomized controlled trial - De Pandis, Maria Francesca; Torti, Margherita; Rotondo, Rossella; Iodice, Lanfranco; Levi Della Vida, Maria; Casali, Miriam; Vacca, Laura; Viselli, Fabio; Servodidio, Valeria; Proietti, Stefania; Stocchi, Fabrizio (Frontiers in Neurology, 2023)
Background: In 1997 the European Parkinson’s Disease Associations launched the Charter for People with Parkinson’s disease that stated the right of patients to be informed and trained on the disease, its course, and treatments available. To date, few data analyzed the effectiveness of education program on motor and non-motor symptoms of PD. Objective: The aim of this study was to evaluate the efficacy of an education program as it was a pharmacological treatment, thus choosing as the primary endpoint the change in daily OFF hours, the most widely used outcome in pharmaceutical clinical trials on PD patients with motor fluctuations. Secondary outcomes were change in motor and non-motor symptoms, quality of life and social functioning. The long-term efficacy of the education therapy was also evaluated by analyzing data collected at 12- and 24-weeks follow-up outpatient visits. Methods: 120 advanced patients and their caregivers were assigned to the intervention or control group in a single-blind, multicentric, prospective, randomized study evaluating an education program structured in individual and group sessions over a 6-weeks period. At the end of study, the intervention group showed a significant reduction in daily OFF hours compared to control patients (−1.07±0.78 vs 0.09 ±0.35, p<0.0001) and a significant improvement was also reported in most secondary outcomes. Patients retained significant medication adherence and daily OFF hours reduction at 12- and 24-weeks follow-up. Conclusions: The results obtained demonstrated that education programs may translate in a notable improvement in motor fluctuations and non-motor symptoms in advanced PD patients. ClinicalTrials.gov Identifier: NCT04378127.